Convict criminology: nový směr vězeňského výzkumu? = Convict criminology : a new way of doing prison research? - Dirga, Lukáš (Česká kriminologie, 2017)
The aim of this paper is to introduce a relatively new and controversial perspective in the field of criminology to Czech readers; the Convict Criminology (or also called the New School of Convict Criminology). Convict Criminology represents especially the work of convicts or ex-convicts, in possession of a Ph.D. or on their way to completing it. After introducing the Convict Criminology, the author discusses methodological possibilities of Convict Criminology in relation to a general level of prison research. Paper is also focused on different kinds of prison researchers and on research collaboration between “inside” and “outside” observer.